2003
DOI: 10.7326/0003-4819-139-5_part_1-200309020-00010
|View full text |Cite
|
Sign up to set email alerts
|

Disappearance of Humoral Thyroid Autoimmunity after Complete Removal of Thyroid Antigens

Abstract: Complete ablation of thyroid tissue with its antigenic components results in the disappearance of antibodies to all major thyroid antigens, thus supporting the concept that continued antibody production depends on the persistence of autoantigen in the body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
2
15

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(132 citation statements)
references
References 9 publications
6
105
2
15
Order By: Relevance
“…Although the patients with the higher initial TgAb concentrations tended to have measurable TgAbs at the end of the study, the within-subject variability was such that no variable could be used to predict persistence of TgAbs 20. With less sensitive agglutination techniques,21 a median time to TgAb disappearance of 3.0 years (95% CI 1.9 to 4.1) was demonstrated.…”
Section: Key Analytical Issuesmentioning
confidence: 95%
“…Although the patients with the higher initial TgAb concentrations tended to have measurable TgAbs at the end of the study, the within-subject variability was such that no variable could be used to predict persistence of TgAbs 20. With less sensitive agglutination techniques,21 a median time to TgAb disappearance of 3.0 years (95% CI 1.9 to 4.1) was demonstrated.…”
Section: Key Analytical Issuesmentioning
confidence: 95%
“…The majority (∼75%) of DTC patients either have no TgAb detected throughout their course or become TgAb-negative in the years following successful surgery [14 ▪ ,27,37 ▪▪ ,89,92,98100]. With RAI treatment now being limited to high-risk DTC patients [13,14 ▪ ,15], most postoperative thyroglobulin testing will be made for low-risk PTC patients with low thyroglobulin concentrations arising from postsurgical thyroid remnants.…”
Section: Postoperative Serum Thyroglobulin Monitoringmentioning
confidence: 99%
“…Some investigations have presented higher frequencies of recurrent or persistent disease related to persistent TgAb (5,8,9,10), but some studies have not demonstrated such correlations (11,12,13). The later prospective investigations have reported that TgAb levels did not affect disease aggravation, and that TgAb diminished gradually after surgery in most cases throughout a three-year follow-up (13,14). …”
Section: Introductionmentioning
confidence: 95%